Magnesium sulphate and sodium bicarbonate as additives for periarticular local infiltration analgesia improve pain management after unicompartmental knee arthroplasty: a prospective, double-blind, randomized controlled trial - Yuchen Zhu; Shaoning Shen; Longkang Cui; Lianguo Wu; Bingbing Zhang (Journal of Orthopaedic Surgery and Research)
Abstract Background Periarticular local infiltration analgesia (LIA) has become a widely used method for postoperative pain management after unicompartmental knee arthroplasty (UKA). However, the efficacy of using magnesium sulphate or sodium bicarbonate in LIA cocktails during UKA is not yet clear. The present study aimed to evaluate whether the modified LIA has advantages in pain control and joint function recovery after UKA surgery. Methods Sixty-one patients who underwent UKA were enrolled and randomly assigned to receive periarticular infiltration of a modified cocktail (comprising ropivacaine, epinephrine, dexamethasone, magnesium sulphate, and sodium bicarbonate) or a conventional cocktail (comprising ropivacaine, epinephrine, dexamethasone, ketorolac, and morphine). The outcomes included the consumption of patient-controlled intravenous analgesia (PCIA) medication used for postoperative analgesia, pain score, early joint functional recovery, discharge time, and complication rates. Results In the first 12 h after surgery, the conventional cocktail was not superior to the modified cocktail in terms of visual analogue scale (VAS) scores. However, beginning on the second postoperative day, the analgesic effect was significantly prolonged in the modified group, leading to lower VAS scores and better knee functional recovery. Additionally, patients in the modified group required less pain medication via PCIA, both within the first 24 h and cumulatively up to 48 h after surgery. Both groups had similar rates of complications. Conclusions The present modification of a conventional cocktail significantly prolonged the analgesic effect and reduced pain medication consumption after UKA surgery, which was associated with better functional recovery in the early postoperative days. Trial registration Chinese Clinical Trial Registry, ChiCTR2200060500. 21 March 2023.